2019
DOI: 10.3892/etm.2019.8169
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic pityriasis rubra pilaris in association with prostate carcinoma: A case report and literature review

Abstract: Pityriasis rubra pilaris (PRP) is a chronic papulosquamous disorder of unknown etiology, characterized by reddish orange scaly plaques, islands of sparing, palmoplantar keratoderma, and keratotic follicular papules. The disease can be acquired or inherited, being divided into 5 categories: classic adult type, atypical adult type, classic juvenile type, circumscribed juvenile type, and atypical juvenile type. More recently, an HIV-associated type has been added to this classification. The cases of PRP associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 19 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…The latest literature states that cases with mild cutaneous adverse reactions (such as lichenoid reactions, granulomatous skin reactions), as in our patient's case, can receive treatment with topical corticosteroids at low doses, moisturizing ointments or oral antihistamines (27,28,30,31). Some patients who developed cutaneous adverse reactions such as vitiligo registered skin repigmentation, not as proof for skin lesion treatment response, but as proof for cancer (melanoma) progression.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The latest literature states that cases with mild cutaneous adverse reactions (such as lichenoid reactions, granulomatous skin reactions), as in our patient's case, can receive treatment with topical corticosteroids at low doses, moisturizing ointments or oral antihistamines (27,28,30,31). Some patients who developed cutaneous adverse reactions such as vitiligo registered skin repigmentation, not as proof for skin lesion treatment response, but as proof for cancer (melanoma) progression.…”
Section: Discussionmentioning
confidence: 72%
“…The latest literature states that cases with mild cutaneous adverse reactions (such as lichenoid reactions, granulomatous skin reactions), as in our patient's case, can receive treatment with topical corticosteroids at low doses, moisturizing ointments or oral antihistamines ( 27 , 28 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, Wang and Orlow summarized KP associations with various neuro-cardio-facial-cutaneous syndromes, ectodermal dysplasias, and neuro developmental disorders, as well as KP-induced drug reactions (11). Differential diagnosis includes a large spectrum of diseases that affect children and adolescents, and which progresses with facial erythema, from habitual erythema, rosacea, atopic dermatitis, comedonal acne, to KP subtypes, including keratosis pilaris rubra faciei, erythromelanosis follicularis faciei et colli, atrophoderma vermiculatum, Darier-White disease, and pityriasis folliculorum (12)(13)(14)). An early diagnosis allows for a targeted treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Fekete et al (13) reported, in a case presentation, the association between paraneoplastic pityriasis rubra pilaris and prostate carcinoma, concluding that PRP can be considered a paraneoplastic syndrome; therefore, tumor screening is mandatory in cases presenting this disease.…”
mentioning
confidence: 99%